2008
DOI: 10.1530/rep-07-0397
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming in embryonic and foetal development upon somatic cell nuclear transfer cloning

Abstract: The birth of 'Dolly', the first mammal cloned from an adult donor cell, has sparked a flurry of research activities to improve cloning technology and to understand the underlying mechanism of epigenetic reprogramming of the transferred somatic cell nucleus. Especially in ruminants, somatic cell nuclear transfer (SCNT) is frequently associated with pathological changes in the foetal and placental phenotype and has significant consequences for development both before and after birth. The most critical factor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(128 citation statements)
references
References 116 publications
0
116
0
10
Order By: Relevance
“…Studies on pre-implantation development of SCNT embryos have shown significant deficiencies in many parts of nuclear events, including transcription and translation, epigenetic modifications such as methylation of DNA, acetylation of histones and chromatin configuration as well as genetic imprinting . In support of these observations, mammalian NT-derived embryos displayed so many abnormalities caused by aberrant expression of genes involved in early development and epigenetic reprogramming (Niemann et al, 2008). However, the amount of data collected associated with gene expression in preimplantation cloned embryos, reconstructed with AMSCs, is limited to a few genes.…”
Section: Introductionmentioning
confidence: 91%
“…Studies on pre-implantation development of SCNT embryos have shown significant deficiencies in many parts of nuclear events, including transcription and translation, epigenetic modifications such as methylation of DNA, acetylation of histones and chromatin configuration as well as genetic imprinting . In support of these observations, mammalian NT-derived embryos displayed so many abnormalities caused by aberrant expression of genes involved in early development and epigenetic reprogramming (Niemann et al, 2008). However, the amount of data collected associated with gene expression in preimplantation cloned embryos, reconstructed with AMSCs, is limited to a few genes.…”
Section: Introductionmentioning
confidence: 91%
“…Also, the abnormal placenta does not produce steroid hormones as it should. Finally, it is often observed abnormal embryo development when using NT or other assisted reproduction techniques and the inability to maintain alive full-term progeny mainly after NT, and these outcomes may be a result of failure during epigenetic reprogramming (NIEMANN et al, 2008;CHAVATTE-PALMER et al, 2012).…”
Section: Pre and Post-natal Clinical Deficiencies Of Animals Producedmentioning
confidence: 99%
“…Pre-and postnatal development is often compromised, and a variable proportion of SCNT offspring show aberrant developmental patterns and increased pre-and perinatal mortality [1]. Aberrant reprogramming of donor somatic cell nuclei may result in many severe problems in animal cloning [2,3]. The interaction between the donor nucleus and the recipient cytoplast plays an important role in the efficiency of SCNT and may influence a number of important biological functions in SCNT during nuclear reprogramming.…”
Section: Introductionmentioning
confidence: 99%